Long-read whole genome sequencing and comparative analysis of six strains of the human pathogen Orientia tsutsugamushi. - Batty, E; Chaemchuen, S; Blacksell, S; Richards, A; Paris, D; Bowden, R; Chan, C; Lachumanan, R; Day, N; Donnelly, P; Chen, S; Salje, J (Public Library of Science, 2018)
Background Orientia tsutsugamushi is a clinically important but neglected obligate intracellular bacterial pathogen of the Rickettsiaceae family that causes the potentially life-threatening human disease scrub typhus. In contrast to the genome reduction seen in many obligate intracellular bacteria, early genetic studies of Orientia have revealed one of the most repetitive bacterial genomes sequenced to date. The dramatic expansion of mobile elements has hampered efforts to generate complete genome sequences using short read sequencing methodologies, and consequently there have been few studies of the comparative genomics of this neglected species. Results We report new high-quality genomes of O. tsutsugamushi, generated using PacBio single molecule long read sequencing, for six strains: Karp, Kato, Gilliam, TA686, UT76 and UT176. In comparative genomics analyses of these strains together with existing reference genomes from Ikeda and Boryong strains, we identify a relatively small core genome of 657 genes, grouped into core gene islands and separated by repeat regions, and use the core genes to infer the first whole-genome phylogeny of Orientia. Conclusions Complete assemblies of multiple Orientia genomes verify initial suggestions that these are remarkable organisms. They have larger genomes compared with most other Rickettsiaceae, with widespread amplification of repeat elements and massive chromosomal rearrangements between strains. At the gene level, Orientia has a relatively small set of universally conserved genes, similar to other obligate intracellular bacteria, and the relative expansion in genome size can be accounted for by gene duplication and repeat amplification. Our study demonstrates the utility of long read sequencing to investigate complex bacterial genomes and characterise genomic variation.